Controlling the Defects of Paint Shop using Seven Quality Control Tools in an Automotive Factory - Memon, I. A.; Ali, A.; Memon, M. A.; Rajput, U. A.; Abro, S. A. K.; Memon, A. A. (Engineering, Technology & Applied Science Research, 2019)
Seven quality control (7QC) tools are used for reducing defects during manufacturing. These tools are highly effective in productivity and quality improvement. In this case, the study of the 7QC tools was applied in an automotive factory in order to reduce paint shop defects. Within four months the production line was inspected, defects were categorized and the 7QC tools were successfully applied, reducing the overall defect rate by 70%. Although every tool was important, the cause and effect diagram was responsible for finding the root causes of the defects.